Notes on the genus Navicordulia Machado & Costa, 1995 (Odonata: Anisoptera: Corduliidae s. str.): description of a new species, phylogenetic affinities and aspects of biogeography - Fleck, Günther (Zootaxa, 2017)
Based on a single male specimen, a remarkable new species of the genus Navicordulia is described from the Massif du Mitaraka in French Guiana (Tumuc-Humac Mountains). Another new species of this genus is also reported from the same locality but is not described. This is the first record of the genus from French Guiana, hitherto being unknown within a radius of more than 1000 km. Apparent rarity or absence of records is probably due to its secretive habits. Navicordulia tumucurakensis sp. nov. presents unique characters not present in other species of the genus including: almost no excavation of the anal angle, proximal sternal pilose ridge of abdominal segment 7 transformed into two large lateral oreillets disconnected from the median carina, additional distal sternal pilose ridge transformed into a medial knob, epiproct not extending beyond the distal half of the cerci, very long cerci surpassing those of described species, cerci lacking ventro-medial carina and tubercle and exhibiting a distal ventral brush of hair-like setae. It is a forest species inhabiting hilly landscapes at low altitude, unlike other closely related intertropical species which are encountered in more elevated areas above 850 m. It is most closely related to N. longistyla, a typical cerrado species from the central Brazilian plateau or possibly to N. nitens from the central south Venezuelan Guaiquinima Tepui. Based on unique derived male abdominal structures and also on the female ovipositor and related structures, the South American genus Navicordulia and the Southeast Asian/Melanesian genus Metaphya are considered current adelphotaxa. This disrupted geographic distribution could be explained by a common ancestor having had a Gondwanian dispersal until the Late Cretaceous or Paleocene.